2020
DOI: 10.3390/electronics9020261
|View full text |Cite
|
Sign up to set email alerts
|

A New CPW-Fed Diversity Antenna for MIMO 5G Smartphones

Abstract: In this study, a new coplanar waveguide (CPW)-fed diversity antenna design is introduced for multiple-input–multiple-output (MIMO) smartphone applications. The diversity antenna is composed of a double-fed CPW-fed antenna with a pair of modified T-ring radiators. The antenna is designed to cover the frequency spectrum of commercial sub-6 GHz 5G communication (3.4–3.8 and 3.8–4.2 GHz). It also provides high isolation, better than −16 dB, without an additional decoupling structure. It offers good potential to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…In this design, the xz plane is H-plane (ϕ = 0 • ) and yz-plane is E-plane (ϕ = 90 • ) for the proposed antenna. From Figure 14, we can see that the antenna can gives dumbbell-like radiation characteristics in E-plane and nearly Omni-directional patterns in H-plane [44,45]. It was found that the radiation patterns of the UWB antenna deteriorate more or less with increasing frequency.…”
Section: Dual-polarized Uwb Slot Antennamentioning
confidence: 96%
“…In this design, the xz plane is H-plane (ϕ = 0 • ) and yz-plane is E-plane (ϕ = 90 • ) for the proposed antenna. From Figure 14, we can see that the antenna can gives dumbbell-like radiation characteristics in E-plane and nearly Omni-directional patterns in H-plane [44,45]. It was found that the radiation patterns of the UWB antenna deteriorate more or less with increasing frequency.…”
Section: Dual-polarized Uwb Slot Antennamentioning
confidence: 96%
“…Table 2 compares the characteristics of the proposed handset antenna design and some reported 5G smartphone MIMO antenna designs in the literature with the recent states of the art [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. To the best of our knowledge, most of the reported sub-6 GHz 5G antennas are single-band operating, and only a few works have reported on the use of the dual-band or multi-band techniques for 5G smartphone applications.…”
Section: Comparisonmentioning
confidence: 99%
“…However, all of these designs either cover only a single-band operation frequency or use a few antenna elements with large sizes which could occupy a huge space of the mainboard. The 5G handset antenna designs introduced in [16][17][18][19][20][21][22][23][24] only cover a single frequency band. In [25][26][27][28][29], dual-band or wideband arrays are proposed to support two 5G spectrums.…”
Section: Introductionmentioning
confidence: 99%
“…Seven articles in this special issue propose novel and efficient antenna designs that employ both single and MIMO synthesis for use in heterogeneous networks [6][7][8][9][10][11][12]. Some of these designs operate on fixed single/multiband and radiations, as in [6][7][8][9][10], while some have the feature of reconfigurability that allows them to operate in a tuned manner in which the resonant frequencies and patterns can be shifted/reconfigured even after the designs have been made [11,12]. The other two articles present recent work on a highly efficient power amplifier which will provide hardware solutions to the growing RF front-end integration challenges with additional design requirements towards energy efficiency for Pas [13,14].…”
Section: The Present Issuementioning
confidence: 99%